Antithrombotic antibacterial compositions and medical devices
Patent Information
- Application Number
- JP2025058613
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2025-03-31
- Publication Date
- 2026-10-14
AI Technical Summary
【0010】 本発明によれば、長期的な抗血栓性、ひいては生体適合性に優れ、かつ、抗菌性が高く、経時着色の少ない抗血栓性抗菌性組成物、コーティング剤、および医療機器を提供することにある。
Smart Images

Figure 2026165947000001 
Figure 2026165947000002 
Figure 2026165947000003
Abstract
Description
[Technical Field]
[0001] This invention relates to an antithrombotic antibacterial composition and a medical device. [Background technology]
[0002] In recent years, research has been progressing on medical devices utilizing various synthetic polymer materials, with potential applications in blood filters, artificial kidney membranes, plasma separation membranes, catheters, artificial lung membranes, artificial blood vessels, adhesion prevention membranes, and artificial skin. In these cases, since synthetic polymer materials, which are foreign to the body, will be used in contact with biological tissues and blood, biocompatibility is required for these medical devices.
[0003] Known biocompatible copolymers include a water-soluble copolymer of polyethylene glycol acrylate and acrylic acrylate (Patent Document 1), and a phosphorylcholine-like group-containing polymer obtained by copolymerizing a hydrophilic (meth)acrylate monomer containing a highly biocompatible phosphorylcholine group with a highly hydrophobic alkyl (meth)acrylate monomer (Patent Document 2).
[0004] Furthermore, medical devices, particularly long-term indwelling medical devices such as high-nutrient infusion catheters, which need to be left in the body for extended periods, require long-term and simultaneous antithrombotic and antibacterial properties to prevent bacteria from multiplying on thrombi formed by contact between blood and the material, and then entering the body and causing infection.
[0005] Therefore, examples of materials that exhibit long-term and simultaneous antithrombotic and antibacterial properties include an antithrombotic antibacterial catheter (Patent Document 3) in which an antithrombotic material is coated on the catheter surface infused with an antibacterial substance, and an antithrombotic antibacterial catheter (Patent Document 4) in which an antithrombotic drug is immobilized. Also, an example is a composition and medical device (Patent Document 5) that imparts long-term antibacterial properties to a polymer that is insoluble in water but exhibits the biocompatibility and blood compatibility of PEG by copolymerizing a (meth)acrylate having a hydrophilic polyethylene glycol (PEG) backbone with a hydrophobic long-chain alkyl (meth)acrylate, by incorporating an antibacterial substance. [Prior art documents] [Patent Documents]
[0006] [Patent Document 1] Japanese Patent Application Publication No. 11-287802 [Patent Document 2] Japanese Patent Application Publication No. 11-35605 [Patent Document 3] Japanese Patent Publication No. 2005-334216 [Patent Document 4] Japanese Patent Application Publication No. 10-211272 [Patent Document 5] Patent No. 5114660 [Overview of the Initiative] [Problems that the invention aims to solve]
[0007] However, Patent Document 3 requires mixing an antimicrobial substance into the base resin that constitutes the catheter, resulting in the antimicrobial substance being present not only on the catheter surface where antimicrobial properties are needed, but throughout the entire catheter, leading to the use of excess antimicrobial substance. Furthermore, Patent Document 4 requires stepwise operation of the extruder if the resin with the antimicrobial substance is to be present only near the catheter surface, complicating the manufacturing process. Moreover, the composition and medical device described in Patent Document 5 may discolor over time, posing challenges for practical use.
[0008] This invention was made against the backdrop of the problems of the prior art. Specifically, it aims to provide an antithrombotic and antibacterial composition, a coating agent, and a medical device in which at least a portion of the blood-contact area is coated with the composition, which exhibit excellent antithrombotic and antibacterial properties and less discoloration over time. [Means for solving the problem]
[0009] In other words, the present invention has the following configuration. [1] (Meth)acrylate copolymer (A) comprising alkyl (meth)acrylate units represented by the following general formula 1 and / or silicone (meth)acrylate units represented by the following general formula 2, and methoxypolyethylene glycol (meth)acrylate units represented by the following general formula 3. and, An antithrombotic antibacterial composition comprising at least one antibacterial substance (B) selected from the group consisting of silver-based inorganic antibacterial agents, zinc oxide-based antibacterial agents, and organic antibacterial agents. [ka] (In the formula, R1 represents an alkyl group having 2 to 30 carbon atoms or an aralkyl group having 7 to 30 carbon atoms, and R2 represents a hydrogen atom or a methyl group.) [ka] (In the formula, R3 is a hydrogen atom or a methyl group, R4 is an alkylene group having 1 to 6 carbon atoms, R5 is an alkyl group having 1 to 6 carbon atoms, and n is in the range of 1 to 1,000.) [ka] (In the formula, R6 represents a hydrogen atom or a methyl group, and m represents a range of 2 to 1,000.) [2] The antithrombotic antibacterial composition according to [1], wherein the antibacterial substance (B) is at least one antibacterial substance selected from silver-based glass antibacterial agents, silver-based zeolite antibacterial agents, and silver-based phosphate antibacterial agents. [3] The antithrombotic antibacterial composition according to [1] to [2], wherein the silver-based inorganic antibacterial agent is an inorganic compound carrying silver and / or silver ions. [4] The antithrombotic antibacterial composition according to [1] to [3], wherein the (meth)acrylate copolymer (A) comprises the alkyl (meth)acrylate unit represented by the general formula 1 and / or the silicone (meth)acrylate unit represented by the general formula 2, and the methoxypolyethylene glycol (meth)acrylate unit represented by the general formula 3, at a molar ratio of (Formula 1 + Formula 2) / Formula 3 = 30 to 90 / 10 to 70. [5] The antithrombotic antibacterial composition according to [1] to [4], wherein the (meth)acrylate copolymer (A) is soluble in any of alcohols having 1 to 6 carbon atoms. [6] The antithrombotic antibacterial composition according to [1] to [5], wherein the glass transition temperature of the (meth)acrylate copolymer (A) is -100 to 20°C. [7] The antithrombotic antibacterial composition according to [1] to [6], wherein the number average molecular weight of the (meth)acrylate copolymer (A) is 2,000 to 200,000. [8] The antithrombotic antibacterial composition according to [1] to [7], wherein the antibacterial substance (B) is contained in an amount of 0.1 mass% to 50.0 mass% relative to the antithrombotic antibacterial composition. [9] The antithrombotic antibacterial composition according to [1] to [8], wherein the antibacterial activity value evaluated based on JIS Z 2801 is 1.3 or more.
[10] A coating agent comprising the antithrombotic antibacterial composition according to any one of [1] to [9].
[11] A medical device, wherein at least a part of a blood contact portion is coated with the antithrombotic antibacterial composition according to any one of [1] to [9]. [Effects of the Invention]
[0010] The present invention aims to provide an antithrombotic antibacterial composition, coating agent, and medical device that exhibit excellent long-term antithrombotic properties, biocompatibility, high antibacterial activity, and minimal discoloration over time. [Modes for carrying out the invention]
[0011] <(meth)acrylate copolymer (A)> The (meth)acrylate copolymer (A) of the present invention is preferably substantially water-insoluble. Here, substantially water-insoluble means that when the (meth)acrylate copolymer (A) is left standing in 99% by mass 37°C physiological saline for 30 days with respect to 1% by mass of the copolymer, the mass loss rate of the copolymer is 1% by mass or less. Being substantially water-insoluble is preferable in that it prevents the copolymer from leaching into blood or other biological tissues when it comes into contact with them.
[0012] (Hydrophobic (meth)acrylate) The (meth)acrylate copolymer (A) preferably contains alkyl (meth)acrylate units represented by the following general formula 1 as hydrophobic (meth)acrylate. [ka] (In the formula, R1 represents an alkyl group having 2 to 30 carbon atoms or an aralkyl group having 7 to 30 carbon atoms, and R2 represents a hydrogen atom or a methyl group.)
[0013] In the present invention, the alkyl (meth)acrylate of general formula 1 preferably has 2 to 30 carbon atoms in R1, more preferably 4 to 24, and even more preferably 6 to 18. Specific examples of such alkyl (meth)acrylates include n-hexyl (meth)acrylate, cyclohexyl (meth)acrylate, phenyl (meth)acrylate, benzyl (meth)acrylate, heptyl (meth)acrylate, octyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, nonyl (meth)acrylate, decyl (meth)acrylate, lauryl (meth)acrylate, myristyl (meth)acrylate, palmityl (meth)acrylate, stearyl (meth)acrylate, etc., but from the viewpoint of cost and performance, 2-ethylhexyl (meth)acrylate or lauryl (meth)acrylate are particularly preferred.
[0014] The (meth)acrylate copolymer (A) more preferably contains a silicone (meth)acrylate unit of the following general formula 2 as the hydrophobic (meth)acrylate. The silicone (meth)acrylate preferably has 1 to 1,000 dimethylsiloxane repeating units, more preferably 1 to 500, even more preferably 10 to 50, and even more preferably 20 to 30. When the number of repeating units is 1 or more, the antithrombotic antibacterial composition is less likely to easily disappear from the coated surface of medical devices. When the number of repeating units is 1,000 or less, the handling of the antithrombotic antibacterial composition is improved. [ka] (In the formula, R3 is a hydrogen atom or a methyl group, R4 is an alkylene group having 1 to 6 carbon atoms, R5 is an alkyl group having 1 to 6 carbon atoms, and n is in the range of 1 to 1,000.)
[0015] The amount of silicone (meth)acrylate added is preferably 0.1% by mass or more, more preferably 0.5% by mass or more, and even more preferably 1.0% by mass or more. When the amount of silicone (meth)acrylate added is 0.1% by mass or more, the antithrombotic properties of the antithrombotic antibacterial composition are exhibited more stably over a longer period. The amount of silicone (meth)acrylate added is preferably 50% by mass or less, more preferably 40% by mass or less, and even more preferably 35% by mass or less, taking into comprehensive consideration performance, quality, cost, etc. Furthermore, silicone (meth)acrylate may be used in mixture with the other alkyl (meth)acrylates mentioned above.
[0016] As stated in "Medical Materials and Functional Membranes" (CMC Publishing), "When medical membrane materials are used in contact with biological tissue or blood, the first phenomenon that occurs is protein adsorption. Protein adsorption to the surface of the medical membrane material is observed immediately after (within 1 second) contact with bodily fluids including blood." Protein adsorption is the first reaction in the body and serves as the starting point for subsequent foreign body recognition reactions. The amount of protein adsorption to a medical device in which at least a portion of the blood-contact area is coated with the antithrombotic antibacterial composition of the present invention is 1.0 μg / m². 2 The following is preferable. If the amount of protein adhesion is within the above range, the foreign body recognition reaction caused by the accumulation of protein adhesion on the surface of the medical device can be suppressed. The amount of protein adhesion is 0.7 μg / m². 2 The following is more preferable: 0.5 μg / m 2 The following is even more preferable: 0.4 μg / m² 2 The following is even more preferable: 0.3 μg / m² 2 The following is particularly preferable: Including silicone (meth)acrylate as the hydrophobic (meth)acrylate is preferable because the hydrophobic properties of silicone help to inhibit protein adhesion.
[0017] (Hydrophilic (meth)acrylate) The (meth)acrylate copolymer (A) preferably contains methoxypolyethylene glycol (meth)acrylate units represented by the following general formula 3 as hydrophilic (meth)acrylate. Methoxypolyethylene glycol (meth)acrylate homopolymers, as seen in the prior art, have high hydrophilicity and therefore excellent blood compatibility, but because they are water-soluble, they gradually dissolve when in contact with blood, etc., for a long period of time, which is disadvantageous in terms of maintaining long-term antithrombotic properties. The inventors of the present invention have diligently studied materials that not only have excellent blood compatibility but can withstand long-term use, and have found that a copolymer obtained by providing appropriate hydrophobicity to prevent dissolution into blood, etc., and flexibility to prevent physical peeling of the coating film can solve this problem. [ka] (In the formula, R6 represents a hydrogen atom or a methyl group, and m represents a range of 2 to 1,000.)
[0018] In the present invention, it is preferable to use a methoxypolyethylene glycol (meth)acrylate of general formula 3 having 2 to 1,000 ethylene oxide units. More preferably, it is 2 to 500, even more preferably 2 to 50, even more preferably 2 to 10, and particularly preferably 2 to 5. If the ethylene oxide units are within the above range, the resistance of the antithrombotic antibacterial composition to elution into blood is improved. Specifically, examples include methoxydiethylene glycol (meth)acrylate, methoxytriethylene glycol (meth)acrylate, methoxytetraethylene glycol (meth)acrylate, methoxypentaethylene glycol (meth)acrylate, methoxyhexaethylene glycol (meth)acrylate, methoxyheptaethylene glycol (meth)acrylate, methoxyoctaethylene glycol (meth)acrylate, methoxynononaethylene glycol (meth)acrylate, and methoxydecaethylene glycol (meth)acrylate. Among these, methoxytetraethylene glycol (meth)acrylate with 4 repeating ethylene oxide units and methoxytriethylene glycol (meth)acrylate with 3 repeating ethylene oxide units are preferred.
[0019] The molar ratio of hydrophobic (meth)acrylate to hydrophilic (meth)acrylate in the (meth)acrylate copolymer (A) is preferably 30-90 / 10-70, more preferably 35-90 / 10-65, even more preferably 40-85 / 15-60, and even more preferably 45-80 / 20-55. If the molar ratio of hydrophobic (meth)acrylate to hydrophilic (meth)acrylate is within the above range, the blood compatibility of the antithrombotic antibacterial composition is improved.
[0020] The alkyl (meth)acrylate units represented by general formula 1, the silicone (meth)acrylate units represented by general formula 2, and the methoxy polyethylene glycol (meth)acrylate units represented by general formula 3 of the (meth)acrylate copolymer (A) are preferably contained in a molar ratio of (formula 1 + formula 2) / formula 3 = 30~90 / 10~70, more preferably 40~90 / 10~60, even more preferably 45~85 / 15~55, and even more preferably 50~80 / 20~50.
[0021] Specific examples of the (meth)acrylate copolymer (A) of the present invention, which consists of alkyl (meth)acrylate and methoxypolyethylene glycol (meth)acrylate, include: n-hexyl (meth)acrylate-methoxydiethylene glycol (meth)acrylate copolymer, n-hexyl (meth)acrylate-methoxytriethylene glycol (meth)acrylate copolymer, n-hexyl (meth)acrylate-methoxytetraethylene glycol (meth)acrylate copolymer, n-hexyl (meth)acrylate-methoxyhexaethylene glycol (meth)acrylate copolymer, n-hexyl (meth)acrylate-methoxytetraethylene glycol (meth)acrylate copolymer, cyclohexyl (meth)acrylate-methoxytriethylene glycol (meth)acrylate copolymer, phenyl (meth)acrylate-methoxytriethylene glycol (meth)acrylate copolymer, phenyl (meth)acrylate-methoxytetraethylene glycol (meth)acrylate copolymer, and phenyl (meth)acrylate-methoxy N-ethylene glycol (meth)acrylate copolymer, n-octyl (meth)acrylate-methoxytriethylene glycol (meth)acrylate copolymer, n-octyl (meth)acrylate-methoxytetraethylene glycol (meth)acrylate copolymer, 2-ethylhexyl (meth)acrylate-methoxydiethylene glycol (meth)acrylate copolymer, 2-ethylhexyl (meth)acrylate-methoxytriethylene glycol (meth)acrylate copolymer, 2-ethylhexyl (meth)acrylate-methoxytetraethylene glycol (meth)acrylate copolymer N-nonyl(meth)acrylate copolymer, lauryl(meth)acrylate-methoxytriethylene glycol(meth)acrylate copolymer, n-nonyl(meth)acrylate-methoxydiethylene glycol(meth)acrylate copolymer, n-nonyl(meth)acrylate-methoxytriethylene glycol(meth)acrylate copolymer, n-nonyl(meth)acrylate-methoxytetraethylene glycol(meth)acrylate copolymer, n-nonyl(meth)acrylate-methoxyhexaethylene glycol(meth)acrylate copolymer,Examples include n-decyl (meth)acrylate-methoxytriethylene glycol (meth)acrylate copolymer, stearyl (meth)acrylate-methoxytriethylene glycol (meth)acrylate copolymer, stearyl (meth)acrylate-methoxyhexaethylene glycol (meth)acrylate copolymer, lauryl (meth)acrylate-methoxytriethylene glycol (meth)acrylate copolymer, and myristyl (meth)acrylate-methoxytriethylene glycol (meth)acrylate copolymer.
[0022] Furthermore, as the (meth)acrylate copolymer (A) of the present invention, specific examples of (meth)acrylates consisting of alkyl (meth)acrylate, silicone (meth)acrylate, and methoxypolyethylene glycol (meth)acrylate include: silicone (meth)acrylate-methoxydiethylene glycol (meth)acrylate copolymer, silicone (meth)acrylate-methoxytriethylene glycol (meth)acrylate copolymer, silicone (meth)acrylate-methoxytetraethylene glycol (meth)acrylate copolymer, silicone (meth)acrylate-n-hexyl (meth)acrylate-methoxydiethylene glycol (meth)acrylate copolymer, silicone (meth)acrylate-n-hexyl (meth)acrylate-methoxytriethylene glycol (meth)acrylate copolymer, silicone (meth)acrylate-n-hexyl (meth)acrylate-methoxytetraethylene glycol (meth)acrylate copolymer, and silicone (meth)acrylate-cyclohexyl (meth)acrylate copolymer. Relate-methoxydiethylene glycol (meth)acrylate copolymer, silicone (meth)acrylate-cyclohexyl (meth)acrylate-methoxytriethylene glycol (meth)acrylate copolymer, silicone (meth)acrylate-cyclohexyl (meth)acrylate-methoxytetraethylene glycol (meth)acrylate copolymer, silicone (meth)acrylate-phenyl (meth)acrylate-methoxydiethylene glycol (meth)acrylate copolymer, silicone (meth)acrylate-phenyl (meth)acrylate-methoxytriethylene glycol (meth)acrylate copolymer, silicone (meth)acrylate-phenyl (meth)acrylate-methoxytriethylene glycol (meth)acrylate copolymer, silicone (meth)acrylate-phenyl (meth)acrylate-methoxytetraethylene glycol (meth)acrylate copolymer, silicone (meth)acrylate-n-octyl (meth)acrylate-methoxydiethylene glycol (meth)acrylate copolymer, silicone (meth)acrylate-n-octyl (meth)acrylate-methoxytriethylene glycol (meth)acrylate copolymer,Silicone (meth)acrylate-n-octyl (meth)acrylate-methoxytetraethylene glycol (meth)acrylate copolymer, silicone (meth)acrylate-2-ethylhexyl (meth)acrylate-methoxydiethylene glycol (meth)acrylate copolymer, silicone (meth)acrylate-2-ethylhexyl (meth)acrylate-methoxytriethylene glycol (meth)acrylate copolymer, silicone (meth)acrylate-2-ethylhexyl (meth)acrylate-methoxytetraethylene glycol (meth)acrylate copolymer, silicone (meth)acrylate-lauryl (meth)acrylate-methoxydiethylene glycol (meth)acrylate copolymer, silicone (meth)acrylate-lauryl (meth)acrylate-methoxytriethylene glycol (meth)acrylate copolymer, silicone (meth)acrylate-lauryl (meth)acrylate-methoxytetraethylene glycol (meth)acrylate copolymer, silicone (meth)acrylate-n-nonyl (meth) Acrylate-methoxydiethylene glycol (meth)acrylate copolymer, silicone (meth)acrylate-n-nonyl (meth)acrylate-methoxytriethylene glycol (meth)acrylate copolymer, silicone (meth)acrylate-n-nonyl (meth)acrylate-methoxytetraethylene glycol (meth)acrylate copolymer, silicone (meth)acrylate-n-decyl (meth)acrylate-methoxydiethylene glycol (meth)acrylate copolymer, silicone (meth)acrylate-n-decyl (meth)acrylate-methoxytriethylene glycol (meth)acrylate copolymer, silicone (meth)acrylate-n-decyl (meth)acrylate-methoxytriethylene glycol (meth)acrylate copolymer, silicone (meth)acrylate-n-decyl (meth)acrylate-methoxytetraethylene glycol (meth)acrylate copolymer, silicone (meth)acrylate-stearyl (meth)acrylate-methoxydiethylene glycol (meth)acrylate copolymer, silicone (meth)acrylate-stearyl (meth)acrylate-methoxytriethylene glycol (meth)acrylate copolymer,Examples include silicone (meth)acrylate-stearyl (meth)acrylate-methoxytetraethylene glycol (meth)acrylate copolymer, silicone (meth)acrylate-lauryl (meth)acrylate-methoxydiethylene glycol (meth)acrylate copolymer, silicone (meth)acrylate-lauryl (meth)acrylate-methoxytriethylene glycol (meth)acrylate copolymer, silicone (meth)acrylate-lauryl (meth)acrylate-methoxytetraethylene glycol (meth)acrylate copolymer, silicone (meth)acrylate-myristyl (meth)acrylate-methoxydiethylene glycol (meth)acrylate copolymer, silicone (meth)acrylate-myristyl (meth)acrylate-methoxytriethylene glycol (meth)acrylate copolymer, and silicone (meth)acrylate-myristyl (meth)acrylate-methoxytetraethylene glycol (meth)acrylate copolymer.
[0023] In the present invention, the number average molecular weight of the (meth)acrylate copolymer (A) is preferably 2,000 or more, more preferably 5,000 or more, and even more preferably 8,000 or more. When the number average molecular weight of the (meth)acrylate copolymer (A) is 2,000 or more, the resistance of the antithrombotic antibacterial composition to elution into blood is improved. The number average molecular weight of the acrylate copolymer (A) is preferably 200,000 or less, more preferably 150,000 or less, even more preferably 100,000 or less, even more preferably 50,000 or less, and particularly preferably 25,000 or less. When the number average molecular weight of the (meth)acrylate copolymer (A) is 200,000 or less, the handling properties when coating medical devices, etc., with the antithrombotic antibacterial composition are improved. Here, the number average molecular weight is the sum of the molecular weights of all molecules divided by the number of molecules, and is one of the properties of polymers.
[0024] Methods for measuring the number-average molecular weight include end-group determination, osmotic pressure method, vapor pressure osmometry, vapor pressure depression method, freezing point depression method, boiling point elevation method, or gel permeation chromatography (GPC). However, in the present invention, gel permeation chromatography (GPC) is preferred due to its ease of operation. Setting the number-average molecular weight of the (meth)acrylate copolymer (A) to 2,000 to 200,000 is a very important technical requirement for achieving specific technical challenges related to the purification of the copolymer, handling of the processing solution, applicability to medical devices, and stability of the coating film.
[0025] In the present invention, it is preferable that the (meth)acrylate copolymer (A) is soluble in any of the alcohols having 1 to 6 carbon atoms. It is more preferable that it is soluble in alcohols having 1 to 3 carbon atoms, as this facilitates drying after coating. Here, solubility means that after adding 1 g of (meth)acrylate copolymer (A) to 10 ml of the alcohol and letting it stand at 25°C for 16 hours, no undissolved (meth)acrylate copolymer (A) can be visually confirmed.
[0026] According to "Basic Polymer Science" (published by Shokodo Co., Ltd. in 1991), when a polymer is cooled from a molten state, it may not crystallize but instead go through a supercooled state and eventually solidify into a glassy state. This transition from the molten state to the glassy state is called the glass transition, and the temperature at which this occurs is called the glass transition temperature. Below the glass transition temperature, the polymer loses its fluidity and becomes glassy, while above the glass transition temperature, it retains fluidity and is essentially in a liquid state. In other words, to give flexibility to the (meth)acrylate copolymer (A) of the present invention, it is preferable to have a glass transition temperature lower than room temperature (25°C).
[0027] The glass transition temperature of the (meth)acrylate copolymer (A) of the present invention is preferably -100 to 20°C. More preferably -80 to 5°C, even more preferably -60 to -10°C, and even more preferably -60 to -25°C. When the glass transition temperature is within the above range, the durability of the antithrombotic antimicrobial composition is improved, and the handling of the antithrombotic antimicrobial composition when coating medical devices, etc., is improved.
[0028] The (meth)acrylate copolymer (A) of the present invention may be a random copolymer, a block copolymer, or a graft copolymer. Furthermore, there are no particular restrictions on the copolymerization reaction itself for producing the copolymer of the present invention, and known methods such as radical polymerization, ionic polymerization, photopolymerization, and polymerization using macromers can be used.
[0029] As an example of how to produce the (meth)acrylate copolymer (A) of the present invention, a method for production by radical polymerization is shown below. Specifically, monomers, polymerization solvent, and initiator are added to a stirable reactor equipped with a reflux column, polymerization is started by purging with nitrogen and heating, and the polymerization is allowed to proceed by maintaining the temperature for a certain period of time. It is more preferable to bubble nitrogen during polymerization. It is also possible to control the molecular weight by using a chain transfer agent in combination with this polymerization. The solvent is removed from the solution after polymerization is complete to obtain a crude (meth)acrylate copolymer. Subsequently, the obtained crude (meth)acrylate copolymer is dissolved in a good solvent and dropped into a poor solvent under stirring to perform a purification treatment (hereinafter sometimes referred to as reprecipitation treatment). The purification treatment is repeated one to several times to increase the purity of the (meth)acrylate copolymer. The (meth)acrylate copolymer obtained in this way is dried.
[0030] As the polymerization solvent used in copolymerization, alcohols such as methanol, ethanol, and isopropyl alcohol, organic solvents such as ethyl acetate, toluene, benzene, and methyl ethyl ketone, or water can be used. However, in the present invention, ethyl acetate, methanol, and ethanol are preferred due to their solubility of the monomer and the resulting copolymer, as well as their availability. Multiple types of the aforementioned solvents can also be mixed and used. The charging mass ratio of these polymerization solvents to monomers is preferably 20-90 / 80-10, more preferably 30-90 / 70-10, and even more preferably 35-85 / 65-15. If the charging ratio is within the above range, the polymerization reaction rate can be maximized.
[0031] As polymerization initiators, peroxide-based and azo-based radical initiators, commonly used in radical polymerization, are employed. Examples of peroxide-based radical initiators include inorganic peroxides such as potassium persulfate, ammonium persulfate, and hydrogen peroxide, and organic peroxides such as benzoyl peroxide, t-butyl hydroperoxide, and cumene peroxide. Examples of azo-based radical initiators include 2,2'-azobisisobutyronitrile, 2,2'-azobis(2-amidinopropane)dihydrochloride, dimethyl 2,2'-azobisbutyrate, and dimethyl 2,2'-azobis(2-methylpropionate). Redox initiators, which combine a peroxide-based initiator with a reducing agent, can also be used. These polymerization initiators are preferably added at a concentration of 0.01 to 1% by mass relative to the monomer in the polymerization solution. More preferably, the addition amount is 0.05 to 0.5% by mass, and even more preferably 0.05 to 0.3% by mass. By adding polymerization initiators and the like within the aforementioned range, copolymers with a good monomer reaction rate and an appropriate number-average molecular weight can be obtained.
[0032] The polymerization temperature varies depending on the type of solvent and initiator, but it is preferable to use a temperature near the 10-hour half-life temperature of the initiator. Specifically, when using the aforementioned initiator, a temperature of 20°C to 120°C is preferred, 30°C to 100°C is more preferred, and 40°C to 90°C is even more preferred. As chain transfer agents used to control the molecular weight during polymerization, high-boiling point thiol compounds such as dodecyl mercaptan, thiomalic acid, and thioglycolic acid, as well as isopropyl alcohol, phosphorous acid, and hypophosphorous acid can be used.
[0033] In the present invention, the (meth)acrylate copolymer (A) is obtained by copolymerizing hydrophilic and hydrophobic monomers, and therefore possesses both hydrophilic and hydrophobic properties. Consequently, the copolymerized solution contains a mixture of unreacted monomers: a hydrophilic monomer (methoxypolyethylene glycol (meth)acrylate), a hydrophobic monomer (alkyl (meth)acrylate), and the (meth)acrylate copolymer. To isolate the water-insoluble (meth)acrylate copolymer from this mixture, for example, the copolymer solution can be purified by dropping it into a reprecipitation solution that dissolves the hydrophilic monomer, and then the copolymer can be purified using a reprecipitation solution that dissolves the hydrophobic monomer. However, such a combination of purification methods is not only cumbersome, but also leads to problems such as high purification costs and significant copolymer loss. The inventors diligently investigated a purification method that is simple, low-cost, and highly recoverable for obtaining (meth)acrylate copolymers, and as a result, found that the (meth)acrylate copolymer can be efficiently recovered by using a reprecipitation poor solvent, which is a mixture of alcohol and water in a specific ratio.
[0034] In the present invention, it is preferable to use a solvent that does not dissolve the copolymer but dissolves both hydrophilic and hydrophobic monomers as the solvent used to purify the copolymer by reprecipitation. If only alcohol is used, it will be necessary to increase or decrease the hydrophilicity of the alcohol compared to the alcohol in order to precipitate the (meth)acrylate copolymer. One method for controlling the hydrophilicity of such an alcohol is to mix it with a highly hydrophilic solvent. Specific examples of such solvents include water, 1,4-dioxane, tetrahydrofuran, N-methylpyrrolidone, N,N-dimethylformamide, and N,N-dimethylacetamide, but water is preferred in terms of safety, ease of operation, volatility, and cost. By mixing alcohol and water in a certain ratio and using it as a poor solvent, the (meth)acrylate copolymer can be obtained simply, at low cost, and with a high recovery rate.
[0035] In the present invention, the alcohol used in the reprecipitation treatment is preferably an alcohol having 1 to 10 carbon atoms, more preferably an alcohol having 1 to 7 carbon atoms, and even more preferably an alcohol having 1 to 4 carbon atoms. Specific examples of such alcohols include methanol, ethanol, 1-propanol, 2-propanol, 1-butanol, 2-butanol, 2-methoxy-1-propanol, and tertiary butanol, but methanol, ethanol, 1-propanol, and 2-propanol are particularly preferred because they allow for low-temperature, short-time drying.
[0036] In the present invention, the reprecipitation solvent is preferably a mixture of an alcohol having 1 to 10 carbon atoms and water in a mass ratio of 40 to 99 / 1 to 60, more preferably 50 to 99 / 1 to 50, even more preferably 60 to 95 / 5 to 40, and particularly preferably 70 to 95 / 5 to 30. When the mass ratio of the alcohol having 1 to 10 carbon atoms and water is within the above range, the purity of the (meth)acrylate copolymer after reprecipitation can be improved.
[0037] In this invention, an embodiment in which a mixture of an alcohol having 1 to 10 carbon atoms and water is used as a poor solvent for reprecipitation will be described in detail. Any good solvent can be used as long as the (meth)acrylate copolymer is dissolved in it and is miscible with the poor solvent. Specifically, examples include tetrahydrofuran, chloroform, acetone, ethyl acetate, N,N-dimethylformamide, N,N-dimethylacetamide, and N-methylpyrrolidone, but tetrahydrofuran and acetone are particularly preferred because they have low boiling points and can be easily dried. It is preferable to purify the product by repeating the reprecipitation treatment multiple times, adding these as good solvents to the poor solvent.
[0038] By performing the reprecipitation operation described above 2 to 8 times as necessary, it is possible to recover a water-insoluble (meth)acrylate copolymer with an unreacted monomer content of less than 5 mol% with a high recovery rate of 50% by mass or more. The unreacted monomer content in the copolymer is preferably 5 mol% or less, more preferably 3 mol% or less, and even more preferably 1 mol% or less. When the unreacted monomer content is within the above range, the safety of the antithrombotic and antibacterial composition to the human body is improved.
[0039] The purified copolymer requires solvent removal by drying. For example, drying can be carried out continuously at 60°C under reduced pressure of 1.0 Torr or less for 2 to 10 days. If sufficient drying is not achieved, vacuum drying can be continued.
[0040] Furthermore, the copolymer of the present invention described above is water-insoluble and can be preferably used as a surface treatment agent to impart antithrombotic properties to medical devices and the like. Specifically, the copolymer can be obtained by dissolving the obtained copolymer in an organic solvent and applying the solution to the surface of a substrate such as a medical device, or by immersing the medical device in the solution and then removing the solvent. Known methods for coating the substrate surface with the copolymer of the present invention include coating methods, methods utilizing graft polymerization by radiation, electron beams, or ultraviolet light, and methods utilizing chemical reactions with the functional groups of the substrate. Among these, the coating method is practically preferred because the manufacturing process is simple. Of course, the medical device material and copolymer may be mixed in advance and then molded into various medical devices. The coating method is not particularly limited, and methods such as coating, spraying, and dipping can be used. For example, the coating method can be carried out by simple operations such as immersing the substrate in a coating solution obtained by dissolving the (meth)acrylate copolymer of the present invention in a suitable organic solvent such as alcohol, chloroform, acetone, tetrahydrofuran, or dimethylformamide, removing the excess solution, and then air-drying. It is also preferable to heat and dry the substrate after coating. This enhances the adhesion between the substrate and the copolymer of the present invention, allowing for stronger fixation. While coating medical devices with the antithrombotic antibacterial composition of the present invention only requires one application of the above treatment, repeating the process multiple times is also within the scope of the present invention, depending on the purpose and application.
[0041] The (meth)acrylate copolymer (A) of the present invention has an appropriate balance of hydrophilicity and hydrophobicity, and therefore exhibits excellent blood compatibility and antithrombotic properties, making it suitable for use as a surface treatment agent for medical devices and artificial organ membranes. Furthermore, because the (meth)acrylate copolymer of the present invention is a viscous substance insoluble in water, even simply coating the surface of medical devices or artificial organ membranes with it does not easily dissolve into the blood, and long-term blood compatibility (antithrombotic) effects can be sustained. Moreover, due to the aforementioned properties of the antithrombotic substance, the sustained release of the antimicrobial substance is appropriately controlled, making it possible to maintain relatively long-term antithrombotic and antimicrobial properties. The (meth)acrylate copolymers of the present invention can be used individually or in mixtures of two or more types.
[0042] When a medical device treated with the (meth)acrylate copolymer (A) of the present invention comes into contact with blood, it is believed that the highly hydrophilic methoxypolyethylene glycol (meth)acrylate protrudes to the surface and exhibits antithrombotic properties, while the alkyl (meth)acrylate remains near the substrate, thereby preventing direct contact between the blood and the medical device.
[0043] In the present invention, aging treatment is used as a method to confirm the water insolubility of the (meth)acrylate copolymer (A). For the extraction solvent used in the aging treatment, physiological saline is preferred in terms of simplicity and improving the reliability of the subsequent blood compatibility evaluation. It is even more preferable to perform the treatment at a constant temperature of 37°C. If the (meth)acrylate copolymer is water insoluble, high blood compatibility is maintained even after the aging treatment.
[0044] In the present invention, a comparison of complement titers is used as a method for evaluating the degree of immunoactivation of (meth)acrylate copolymer (A). The Mayer method for measuring CH50 (see Artificial Organs 23(3), 654-659 (1994)) is preferred because it allows for simple and rapid measurement, and the measurement kit is readily available and inexpensive. Sensitized red blood cells react with complement in the serum, causing hemolysis of the sensitized red blood cells. Since the degree of hemolysis decreases as the complement system is activated, this method can be significantly utilized as an evaluation method.
[0045] <Antibacterial substance (B)> The antimicrobial substance (B) of the present invention is selected from the group consisting of silver-based inorganic antimicrobial agents, zinc oxide-based antimicrobial agents, and organic antimicrobial agents, and two or more antimicrobial substances may be used in combination. In particular, silver-based inorganic antimicrobial agents are preferred from the viewpoint of high antimicrobial activity, stability, and safety. Among silver-based inorganic antimicrobial agents, silver-based glass antimicrobial agents, silver-based zeolite antimicrobial agents, and silver-based phosphate antimicrobial agents are more preferred from the viewpoint of antimicrobial activity, discoloration resistance, cost, etc.
[0046] Silver-based inorganic antibacterial agents are those in which silver and / or silver ions are supported on an inorganic compound (such as glass, zeolite, or phosphate). Examples of inorganic compounds used as the support include soluble glass (soluble glass is a general term for glass with a dissolution rate controlled by its composition), zeolite, zirconium phosphate, calcium phosphate, calcium apatite, silica gel, calcium silicate, magnesium aluminosilicate, titanium dioxide, potassium titanate, silica, alumina, and thiosulfite. From the viewpoint of antibacterial activity, discoloration resistance, and cost, the use of silver-based glass antibacterial agents in which silver is supported on soluble glass, silver-based zeolite antibacterial agents in which silver is supported on zeolite, and silver-based phosphate antibacterial agents in which silver is supported on calcium phosphate is preferred.
[0047] In this context, silver-based inorganic antibacterial agents exert a sustained antibacterial effect through the sustained release of silver and / or silver ions supported on the inorganic compound. On the other hand, silver nanoparticle-based antibacterial agents, silver oxide-based antibacterial agents, and silver complex-based antibacterial agents are distinguished from silver-based inorganic antibacterial agents because they are not supported on an inorganic compound, and the silver nanoparticles, silver oxide, and silver ion complexes themselves function as antibacterial components.
[0048] Silver nanoparticle-based antibacterial agents, silver oxide-based antibacterial agents, and silver complex-based antibacterial agents are commonly used, but they discolor significantly over time and are unsuitable for use in antithrombotic antibacterial compositions.
[0049] Zinc oxide-based antimicrobial agents generally have lower antimicrobial activity compared to silver-based antimicrobial agents, but they are characterized by lower cost, high safety and stability, and no discoloration over time, making them suitable for use. They also have biofilm-inhibiting ability, but in cases where long-term durability is desired, using silver-based inorganic antimicrobial agents is more preferable.
[0050] Organic antimicrobial agents offer faster action and cost advantages compared to inorganic antimicrobial agents, but in cases where long-term durability is desired, using silver-based inorganic antimicrobial agents is more preferable.
[0051] The organic antibacterial agent is not particularly limited, and any antibacterial substance may be used. For example, ampicillin, naphthillin, amoxicillin, oxacillin, azurocillin, penicillin G, carbenicillin, penicillin V, dicloxacillin, pheneticillin, floxacillin, piperacillin, mecillinum, sulbenicillin, methicillin, ticarcillin, mezlocillin, cefacrol, cephalothin, cefadroxil, cefapillin, cefamandol, cefarazine, cefatolidine, cefsulozin, cefazolin, Phthazidime, Cephoranide, Ceftriaxone, Cefoxitin, Cefuroxime, Cefacetril, Latamoxef, Cephalexin, Amikacin, Neomycin, Dibekacin, Kanamycin, Gentamicin, Netylmycin, Kanamycin, Tobramycin, Amphotericin B, Novobiocin, Bacitracin, Nistatin, Clindamycin, Polymyxin, Colistin, Rovamycin, Erythromycin, Streptomycin, S Examples include antibiotics such as pectinomycin, lincomycin, vancomycin, chlortetracycline, oxytetracycline, demeclocycline, lolitetracycline, doxycycline, tetracycline, and minocycline; antifungal agents such as amphotericin B, ketoconazole, clotrimazole, miconazole, econazole, natamycin, flucytosine, nistatin, and griseofulvin; parahydroxybenzoic acid esters such as isobutyl parahydroxybenzoate, isopropyl parahydroxybenzoate, ethyl parahydroxybenzoate, butyl parahydroxybenzoate, and propyl parahydroxybenzoate; biguanide compounds such as chlorhexidine; surface-active compounds such as benzethonium, benzalkonium, lauryl sulfate, alkylpolyaminoethylglycine, fatty acids, and domiphene bromide; and phenol derivatives such as thymol, phenol, hexachlorophene, and resorcinol. These antimicrobial substances may be salt compounds such as sodium salts, potassium salts, magnesium salts, calcium salts, hydrochloride salts, sulfate salts, and gluconate salts, and two or more antimicrobial substances may be used in combination.
[0052] When the surface of a medical device is coated with the composition of the present invention, a coating layer is formed containing a water-insoluble antithrombotic substance ((meth)acrylate copolymer) and a poorly water-soluble antimicrobial substance. It is unclear whether this is because the copolymer is water-insoluble, or because the water-insolubleness of the copolymer and the poor water solubility of the antimicrobial substance function complementaryly, but the elution of the antimicrobial substance is extremely slow and sustained, allowing for long-term antimicrobial activity to be maintained. On the other hand, when a copolymer and a water-soluble antimicrobial substance are coated, although the copolymer is water-insoluble, the antimicrobial substance is water-soluble, so the elution rate is higher than when a poorly water-soluble antimicrobial substance is used. As a result, strong antimicrobial activity can be exhibited in the short term, but long-term antimicrobial activity cannot be maintained. For example, intravascular catheters, infusion tubes, and artificial lungs are medical devices that are used continuously for one to several days, and long-term sustained antimicrobial activity is necessary for such applications. Furthermore, by using both water-soluble and poorly water-soluble antibacterial substances in combination, it is possible to impart multi-stage antibacterial properties. Initially, the water-soluble antibacterial substance exhibits strong bactericidal activity, and then the poorly water-soluble antibacterial substance provides long-term antibacterial activity. Applying this multi-stage antibacterial property to intravascular catheters is expected to reduce the risk of infection during insertion by allowing the water-soluble antibacterial substance to dissolve early and exhibit strong antibacterial activity, thereby killing skin commensal bacteria that may be introduced into the bloodstream during catheter insertion. During catheter placement, the long-term antibacterial activity of the poorly water-soluble antibacterial substance can prevent bacterial colonization of the catheter and the proliferation of bacteria that have entered from the insertion site, further reducing the risk of infection during placement. Examples of poorly water-soluble antibacterial substances include silver-based antibacterial agents, zinc oxide-based antibacterial agents, and chlorhexidine. Examples of water-soluble antibacterial substances include benzalkonium, penicillin G potassium (potassium salt of penicillin G), and streptomycin sulfate (sulfate of streptomycin).
[0053] In the present invention, the antimicrobial substance is preferably 0.01 to 70% by mass, more preferably 0.05 to 60% by mass, and even more preferably 0.1 to 50% by mass, relative to the mass of the antithrombotic antimicrobial composition. When the antimicrobial substance is within the above range, the antithrombotic antimicrobial composition exhibits high antimicrobial activity, and the appearance of the antithrombotic antimicrobial composition when coated onto a medical device is good.
[0054] <Coating agent> The antithrombotic and antibacterial composition of the present invention obtained as described above can be used as a coating agent containing it. This coating agent can be prepared by adding a suitable solvent to the antithrombotic and antibacterial composition.
[0055] The type and concentration of solvent used in the coating agent of the present invention can be appropriately selected depending on the composition and molecular weight of the antithrombotic antibacterial composition, the type of substrate to be coated, and its surface properties.
[0056] In the present invention, the method for coating a medical device with an antimicrobial substance is not particularly limited. 1) The antimicrobial substance may be coated onto the medical device after the antithrombotic substance (polymer) has been applied. 2) The antimicrobial substance may be coated onto the medical device first, and then the antimicrobial substance (polymer) may be applied. 3) The antimicrobial substance and the antimicrobial substance may be pre-mixed, dissolved, or dispersed in an organic solvent or the like, and then coated onto the medical device. The concentration of the antithrombotic antimicrobial composition in the coating solution is preferably 0.005 to 2.5% by mass, and more preferably 0.01 to 2.0% by mass. When the concentration of the antithrombotic antimicrobial composition in the coating solution is within the above range, the handling of the antithrombotic antimicrobial composition when coating the medical device is improved, and the antimicrobial properties of the medical device are improved.
[0057] In the present invention, it is preferable that the antibacterial activity after 7 days is 2.0 or higher when evaluated by the antibacterial test described later. If the antibacterial activity after 7 days is 2.0 or higher, it can be determined that sufficient antibacterial activity is maintained even in medical devices intended for long-term use. A higher antibacterial activity value indicates superior antibacterial properties, so 3.0 or higher is more preferable, 4.0 or higher is even more preferable, and 5.0 or higher is even more preferable.
[0058] The solvent used in the coating agent is not particularly limited as long as it dissolves the antithrombotic and antibacterial composition. For example, methanol, ethanol, isopropyl alcohol, n-propyl alcohol, acetone, n-hexane, cyclohexane, tetrahydrofuran, 1,4-dioxane, cyclohexanone, N,N-dimethylformamide, N,N-dimethylacetamide, N-methylpyrrolidone, etc., can be used. Among these, methanol, ethanol, and isopropyl alcohol are more preferred because they have low boiling points and dry easily after coating. Furthermore, in order to more uniformly disperse the antibacterial substance, it is more preferable to use a mixture of these organic solvents with water or ammonia water as the solvent for the antithrombotic and antibacterial composition. These solvents may be used individually or in combination of two or more as needed.
[0059] The coating agent of the present invention may contain a crosslinking agent in addition to the above-mentioned antithrombotic and antibacterial composition and solvent. The crosslinking agent can crosslink the copolymer, further improving the copolymer's resistance to bodily fluids. Furthermore, the functional groups present on the surface of the medical device may be crosslinked with the copolymer, potentially suppressing the detachment of the copolymer from the medical device.
[0060] Examples of crosslinking agents include compounds having two or more reactive functional groups. Reactive functional groups are those that can react with carboxyl groups, such as isocyanate groups, amino groups, and epoxy groups. Specific examples include diphenylmethane diisocyanate (MDI), trimethylolpropane adduct of tolylene diisocyanate, trimethylolpropane adduct of hexamethylene diisocyanate, and diethylenetriamine.
[0061] The concentration of the crosslinking agent can be adjusted as appropriate, but for example, it can be added at a concentration of 5% to 50% by mass relative to the antithrombotic antibacterial composition.
[0062] <Medical devices> Another aspect of the present invention is a medical device in which at least a portion of the blood-contacting portion is coated with the (meth)acrylate copolymer that imparts the antibacterial properties of the present invention. Preferably, in the medical device of the present invention, at least a portion of the surface, preferably all of the portion of the surface that comes into contact with blood, etc., is treated with the (meth)acrylate copolymer of the present invention. One preferred aspect of the medical device of the present invention is that it is required to have excellent antithrombotic and antibacterial properties. Examples of such medical devices include blood filters, blood storage containers, blood circuits, indwelling needles, catheters, guidewires, stents, artificial lung devices, dialysis machines, adhesion prevention materials, wound dressings, adhesives for biological tissues, and repair materials for biological tissue regeneration. It is particularly effective for medical devices that need to be implanted for a long period of time and are likely to cause infections.
[0063] This includes all materials commonly used as substrates for medical devices. These include polyvinyl chloride, polycarbonate, polyethylene terephthalate, polyethylene, polypropylene, poly-4-methylpentene-1, thermoplastic polyether polyurethane, thermosetting polyurethane, silicone rubber such as polydimethylsiloxane with crosslinking, polymethyl methacrylate, polyvinylidene fluoride, tetrafluoroethylene, polysulfone, polyethersulfone, polyacetal, polystyrene, ABS resin and mixtures of these resins, and metals such as stainless steel, titanium, and aluminum. [Examples]
[0064] The present invention will be described in detail below with reference to examples, but the present invention is not limited thereto.
[0065] <Evaluation and Measurement of (meth)acrylate copolymers> (Measurement of number-average molecular weight (Mn)) 15 mg of the sample was dissolved or diluted with 3 mL of mobile phase for GPC measurement, and the sample was filtered through a hydrophilic polytetrafluoroethylene (PTFE) membrane with a pore size of 0.45 μm (Millex-LH, Millipore Japan). The GPC measurement was performed using a 510 high-pressure pump, a 717plus automatic injector (Waters Corporation Japan), and an RI-101 (Showa Denko Corporation) analyzer. The column was PLgel 55 μMIXED-D (600 × 7.5 mm) (Polymer Laboratories), the column temperature was room temperature, and the mobile phase was tetrahydrofuran (THF) with 0.03 mass% dibutylhydroxytoluene (BHT) added. Detection was performed using radioisotopes, and 50 μL was injected. The molecular weight composition was monodisperse polymethyl methacrylate (PMMA) (EasiCal: Polymer Laboratories).
[0066] (Viscosity measurement) The test was performed using a BII-type viscometer (BHII type, Toki Sangyo). A container containing 200g of the sample was left to stand in a water bath set to 37°C for 1 hour. Three measurements were then taken (rotor No. 7, rotation speed 2 rpm), and the average value was taken as the viscosity (Pa·s) value.
[0067] (Measurement of copolymerization composition ratio) 50 mg of the sample was added to an NMR test tube (standard; N-5, Nippon Seimitsu Kagaku Co., Ltd.) using a Pasteur pipette, then 0.7 mL of deuterated chloroform (Wako Pure Chemical Industries, Ltd.) was added and thoroughly mixed, and the tube was capped with a sample cap (standard NC-5, Nippon Seimitsu Kagaku Co., Ltd.). The copolymerization ratio was determined at room temperature using a BRUKER ADVANCE NEO 600. 1 The results were calculated by performing 1H-NMR measurements.
[0068] (Measurement of remaining unreacted monomers) 50 mg of the sample was added to an NMR test tube (standard; N-5, Nippon Seimitsu Kagaku Co., Ltd.) using a Pasteur pipette, then 0.7 mL of deuterated chloroform (Wako Pure Chemical Industries, Ltd.) was added and thoroughly mixed, and the tube was capped with a sample cap (standard NC-5, Nippon Seimitsu Kagaku Co., Ltd.). The copolymerization ratio was determined at room temperature using a BRUKER ADVANCE NEO 600. 1 The unreacted monomers in the (meth)acrylate copolymer were calculated from the integral ratio obtained by 1H-NMR measurement.
[0069] (Alcohol solubility test) 1 g of the sample and 10 mL of any C1-C6 alcohol were added to a 50 mL vial and thoroughly mixed. The mixture was then allowed to stand at 25°C for 16 hours. Afterwards, the vial was marked "○" if no undissolved sample remained visible, and "×" if undissolved sample was visible.
[0070] (Water insolubility test) A 0.1g sample was taken, 9.9g of physiological saline was added, and the mixture was allowed to stand at 37°C for 30 days. The precipitate was washed with distilled water, freeze-dried, and then the dissolved amount was weighed. Samples with a mass loss rate of 1% by mass or less were marked with "○".
[0071] (Measurement of glass transition temperature) A differential scanning calorimeter (Shimadzu DSC-50) was used. 10 mg of the sample was packed into a cell (Al cell, 6 mmφ, Shimadzu Corporation), capped, crimped and sealed with a sealer / crimper (Shimadzu Corporation), and then set in the measuring instrument for measurement. After cooling with liquid nitrogen, the measurement was carried out from -150°C to 60°C under an N2 gas flow at a heating rate of 5°C / min. In the endothermic curve obtained during this process, the temperature at the intersection of the baseline before the endothermic peak and the tangent line toward the endothermic peak was defined as the glass transition temperature (Tg, unit: °C).
[0072] <Evaluation and measurement of antithrombotic and antimicrobial compositions> (Blood compatibility assessment - sample preparation) A surface treatment agent was used, which was obtained by dissolving or dispersing a copolymer and an antibacterial substance in ethanol. A 25 × 25 × 1 mm PVC sheet was immersed in the obtained surface treatment agent, then the sheet was removed and dried at 60°C for 24 hours to obtain a pre-aging sample for blood compatibility testing. Furthermore, the sheet was aged in physiological saline at 37°C for 30 days to obtain a post-aging sample for blood compatibility testing. The mass of the PVC sheet was denoted as W0, the mass of the pre-aging sample as W1, and the mass of the post-aging sample as W2. The mass loss rate (%) was calculated based on the following formula. A mass loss rate of 20% by mass or less was marked as "○", and a mass loss rate greater than 20% by mass was marked as "×". If the mass loss rate exceeds 20% by mass, it can be judged that it has dissolved significantly in physiological saline even considering measurement errors. Mass reduction rate (%)=((W2-W0) / (W1-W0))×100
[0073] (Blood compatibility assessment test) 60 mL of citrate-treated fresh blood drawn from a rabbit was divided equally into two 50 mL centrifuge tubes and centrifuged at 1000 rpm for 10 minutes. The supernatant was divided equally into four 10 mL centrifuge tubes. After further centrifuging at 1500 rpm for 10 minutes, the supernatant was removed and the platelet pellet (precipitate) was separated. By adding HBSS (Hanks equilibrium salt solution) and diluting it, a platelet concentration of 3.0 × 10⁶ was obtained. 8A platelet solution of cells / mL was obtained. The platelet concentration was confirmed using a hemocytometer (KX-21, Sysmex Corporation). The platelet solution at this concentration was used as the test solution. 0.2 mL of the obtained test solution was taken and dripped onto the upper surface of an aged sample for blood compatibility test in a 60 mm × 15 mm petri dish (Corning Incorporated, made of polystyrene), then the dish was covered and incubated at 37°C for 1 hour. Thereafter, 5 mL of a 2.5 mass% glutaraldehyde aqueous solution was added, and the mixture was allowed to stand at room temperature for 24 hours. After the operation of replacing the solution in the petri dish with water was performed 3 times, the water was removed. The water-washed vinyl chloride sheet was frozen at -5°C for 24 hours, and then dried at 0.1 Torr for 24 hours. A 10 mm × 10 mm piece was cut out from the portion where platelets had adhered, and was affixed to a sample stage for a scanning electron microscope (SEM) with double-sided adhesive tape to serve as a measurement sample. Using the sample subjected to ion deposition, the state of adhered platelets was photographed by SEM. The photographed SEM images (at 3000× magnification) were visually compared and observed, and the case where the number of adhered platelets was 50 or less was evaluated as good.
[0074] (Complement titer evaluation - Sample preparation) A solution obtained by dissolving or dispersing the copolymer and the antibacterial substance in ethanol was used as a surface treatment agent. After immersing 1 g of glass beads with a diameter of 1 mm in the obtained surface treatment agent, the glass beads were taken out and dried at 60°C for 24 hours. Further, aging was performed in 37°C physiological saline for 30 days to obtain a sample for complement titer evaluation.
[0075] (Complement titer evaluation - Measurement) 10 mL of fresh human blood dispensed into a 50 mL polypropylene centrifuge tube (IWAKI & Co., Ltd.) was allowed to stand at room temperature to coagulate, and centrifuged at 3000 rpm for 30 minutes (using LC06, TOMY SEIKO CO., LTD.) to obtain 3.5 mL of serum. After 0.1 mL of diluent was added to the sample for complement titer evaluation, the mixture was incubated at 37°C for 1 hour, 0.2 mL of the obtained serum was further added, and incubation was performed at 37°C for 1 hour. Diluent (Ca 2+ and Mg 2+2.6 mL of Veronal buffer (containing [ingredient]), 12.5 μL of serum in contact with the complement evaluation sample, and 0.4 mL of sensitized sheep erythrocytes were thoroughly mixed, incubated at 37°C for 1 hour, cooled at 0°C for 10 minutes, and then centrifuged at 2000 rpm. The absorbance of 2 mL of the supernatant was measured at 541 nm using a HITACHI "U-2000 Spectrometer". Simultaneously, data from samples with 2.6 mL of diluent and 0.4 mL of sensitized sheep erythrocytes added were subtracted as samples without hemolysis. Auto CH50-L "Seiken" (unified product number 400437, 52 mL of diluent, 6 mL of sensitized sheep erythrocytes) was used as the diluent and sensitized sheep erythrocytes. Relative absorbance was calculated with the absorbance value of an untreated glass sphere set to 1, and values of 1.2 or higher were considered good, while values below 1.2 were considered poor. If the value is less than 1.2, it can be concluded that the complement system was significantly activated, even after considering measurement errors.
[0076] (Antibacterial test) A surface treatment agent was used, which was obtained by dissolving or dispersing a copolymer and an antimicrobial substance in ethanol. A 50mm x 50mm x 0.3mm polyethylene film was immersed in the resulting surface treatment agent for 5 seconds, then removed and dried at 60°C for 24 hours to obtain a sample before aging for antimicrobial testing. Furthermore, the sample was aged in physiological saline at 37°C for 7 days to obtain a sample after aging for antimicrobial testing. Antimicrobial activity was evaluated according to JIS Z 2801. In this antimicrobial test, the antimicrobial activity value can be calculated from the number of viable bacteria, and if the antimicrobial activity value is 2.0 or higher, an antimicrobial effect is considered to have been obtained.
[0077] (Appearance after coating) A surface treatment agent was used, which was obtained by dissolving or dispersing a copolymer and an antibacterial substance in ethanol. A 50mm x 50mm x 0.3mm polyethylene film was immersed in the obtained surface treatment agent for 5 seconds, then the film was removed and dried at 60°C for 24 hours to obtain a post-coating appearance test sample (before aging). Furthermore, the film was aged in physiological saline at 37°C for 7 days to obtain a post-coating appearance test sample (after aging). The appearance test was performed visually, and samples with uneven coating were judged to be defective. In addition, samples that developed uneven coating or showed changes in hue such as discoloration after aging were judged to be defective.
[0078] <Synthesis of methacrylate copolymers> (Manufacturing Example 1) In a stirable reactor equipped with a reflux column, 17.1 g of methoxytriethylene glycol acrylate (MTEGA) (Shin-Nakamura Chemical Co., Ltd.), 10.2 g of silicone methacrylate represented by the following general formula 4 (Shin-Etsu Silicone Co., Ltd., product name: X-24-8201, number average molecular weight: 2,100), 23.9 g of lauryl acrylate (Shin-Nakamura Chemical Co., Ltd.), 0.052 g of azobisisobutyronitrile (AIBN) (Wako Pure Chemical Industries, Ltd.), and 200.2 g of ethyl acetate (Tokyo Chemical Industries, Ltd.) were added, and the polymerization reaction was carried out at a set temperature of 80°C for 20 hours. After the polymerization reaction was completed, the polymerization solvent was removed by evaporation at 60°C and 0.1 Torr for 4 days to obtain crude (meth)acrylate polymer (A-1). [ka]
[0079] Two g of the obtained crude (meth)acrylate polymer (A-1) was dissolved in two g of tetrahydrofuran and added dropwise to 20 g of poor solvent (methanol / water = 85 / 15 (mass ratio)) under stirring using a Pasteur pipette. The precipitate was collected by decantation, and the same mass of tetrahydrofuran was added to dissolve it. This procedure of adding the precipitate dropwise to the poor solvent was repeated twice, and then the mixture was dried under reduced pressure at 60°C and 0.1 Torr for four days to obtain (meth)acrylate polymer (A-1). The composition and properties of (meth)acrylate polymer (A-1) are summarized.
[0080] (Manufacturing example 2) In a stirable reactor equipped with a reflux column, 15.1 g of methoxytriethylene glycol acrylate (MTEGA) (Shin-Nakamura Chemical Co., Ltd.), 29.7 g of 2-ethylhexyl acrylate (EHA) (Tokyo Chemical Industries Co., Ltd.), 0.0447 g of azobisisobutyronitrile (AIBN) (Wako Pure Chemical Industries, Ltd.), and 178.9 g of ethanol (Wako Pure Chemical Industries, Ltd.) were added, and the polymerization reaction was carried out at a set temperature of 80°C for 20 hours. After the polymerization reaction was completed, the polymerization solvent was removed by evaporation at 60°C and 0.1 Torr for 4 days to obtain crude (meth)acrylate polymer (A-2).
[0081] Two g of the obtained crude (meth)acrylate polymer (A-2) was dissolved in two g of tetrahydrofuran and added dropwise to 20 g of poor solvent (methanol / water = 85 / 15 (mass ratio)) under stirring using a Pasteur pipette. The precipitate was collected by decantation, and the same mass of tetrahydrofuran was added to dissolve it. This process of adding the precipitate dropwise to the poor solvent was repeated twice, and then the polymer was dried under reduced pressure at 60°C and 0.1 Torr for four days to obtain (meth)acrylate polymer (A-2). The composition and properties of (meth)acrylate polymer (A-2) are summarized.
[0082] (Manufacturing Example 3) In a stirable reactor equipped with a reflux column, 10.2 g of methoxynonaethylene glycol acrylate (MNEGA) (Shin-Nakamura Chemical Co., Ltd.) and 42.3 g of silicone methacrylate (Shin-Etsu Silicone Co., Ltd., product name: X-24-8201, number average molecular weight: 2,100) were added to 0.047 g of azobisisobutyronitrile (AIBN) (Wako Pure Chemical Industries, Ltd.), and the polymerization reaction was carried out in 200.5 g of ethyl acetate (Tokyo Chemical Industries, Ltd.) at a set temperature of 80°C for 20 hours. After the polymerization reaction was completed, the polymerization solvent was removed by evaporation at 60°C and 0.1 Torr for 4 days to obtain crude (meth)acrylate polymer (A-3).
[0083] Two g of the obtained crude (meth)acrylate polymer (A-3) was dissolved in two g of tetrahydrofuran and added dropwise to 20 g of poor solvent (methanol / water = 85 / 15 (mass ratio)) under stirring using a Pasteur pipette. The precipitate was collected by decantation, and the same mass of tetrahydrofuran was added to dissolve it. This process of adding the precipitate dropwise to the poor solvent was repeated twice, and then the mixture was dried under reduced pressure at 60°C and 0.1 Torr for four days to obtain (meth)acrylate polymer (A-3). The composition and properties of (meth)acrylate polymer (A-3) are summarized.
[0084] (Manufacturing example 4) In a stirable reactor equipped with a reflux column, 36.6 g of methoxynonaethylene glycol acrylate (MNEGA) (Shin-Nakamura Chemical Co., Ltd.), 10.2 g of silicone methacrylate represented by general formula 4 (Shin-Etsu Silicone Co., Ltd., product name: X-24-8201, number average molecular weight: 2,100), and 23.9 g of lauryl acrylate (Shin-Nakamura Chemical Co., Ltd.) were added to 0.052 g of azobisisobutyronitrile (AIBN) (Wako Pure Chemical Industries, Ltd.). The polymerization reaction was carried out in 200.2 g of ethyl acetate (Tokyo Chemical Industries, Ltd.) at a set temperature of 80°C for 20 hours. After the polymerization reaction was completed, the polymerization solvent was removed by evaporation at 60°C and 0.1 Torr for 4 days to obtain crude (meth)acrylate polymer (A-4).
[0085] Two g of the obtained crude (meth)acrylate polymer (A-4) was dissolved in two g of tetrahydrofuran and added dropwise to 20 g of poor solvent (methanol / water = 85 / 15 (mass ratio)) under stirring using a Pasteur pipette. The precipitate was collected by decantation, and the same mass of tetrahydrofuran was added to dissolve it. This procedure of adding the precipitate dropwise to the poor solvent was repeated twice, and then the mixture was dried under reduced pressure at 60°C and 0.1 Torr for four days to obtain (meth)acrylate polymer (A-4). The composition and properties of (meth)acrylate polymer (A-4) are summarized.
[0086] (Manufacturing example 5) In a stirable reactor equipped with a reflux column, 22.3 g of 2-ethylhexyl acrylate (EHA) (Tokyo Chemical Industries, Ltd.) was added to 0.0467 g of azobisisobutyronitrile (AIBN) (Wako Pure Chemical Industries, Ltd.), and 100 g of ethyl acetate (Tokyo Chemical Industries, Ltd.) was added. The polymerization reaction was carried out at a set temperature of 80°C for 20 hours. The resulting polymerization solution was added dropwise to methanol under stirring using a Pasteur pipette to obtain a crude (meth)acrylate polymer (A-5).
[0087] 2 g of crude (meth)acrylate polymer (A-5) was dissolved in 2 g of tetrahydrofuran and added dropwise to 20 g of poor solvent (methanol) under stirring using a Pasteur pipette. The precipitate was collected by decantation, and the same mass of tetrahydrofuran was added to dissolve it. This process of adding the precipitate dropwise to the poor solvent was repeated twice, and then the mixture was dried under reduced pressure at 60°C and 0.1 Torr for 4 days to obtain (meth)acrylate polymer (A-5). The composition and properties of (meth)acrylate polymer (A-5) are summarized.
[0088] (Manufacturing example 6) In a stirable reactor equipped with a reflux column, 25.6 g of methoxymonoethylene glycol acrylate (MMEGA) (Tokyo Chemical Industries, Ltd.), 0.0246 g of azobisisobutyronitrile (AIBN) (Wako Pure Chemical Industries, Ltd.), and 119.1 g of dimethylacetamide (Kishida Chemical Co., Ltd.) were added, and the polymerization reaction was carried out at a set temperature of 80°C for 20 hours. The resulting polymerization solution was added dropwise to n-hexane under stirring using a Pasteur pipette to obtain a crude (meth)acrylate polymer (A-6).
[0089] 2 g of crude (meth)acrylate polymer (A-6) was dissolved in 2 g of tetrahydrofuran and added dropwise to 20 g of poor solvent (n-hexane) under stirring using a Pasteur pipette. The precipitate was collected by decantation, and the same mass of tetrahydrofuran was added to dissolve it. This process of adding the precipitate dropwise to the poor solvent was repeated twice, and then the mixture was dried under reduced pressure at 60°C and 0.1 Torr for 4 days to obtain (meth)acrylate polymer (A-6). The composition and properties of (meth)acrylate polymer (A-6) are summarized below.
[0090] <Preparation of antithrombotic antibacterial compositions> (Example 1) A surface treatment agent was prepared by dissolving (meth)acrylate polymer (A-1) in ethanol to a solid content concentration of 3 wt%, then adding the silver-based phosphate antibacterial agent Novalon AG300 (manufactured by Toagosei Co., Ltd.) as the antibacterial substance (B-1), and stirring with an ultrasonic device for 5 minutes. At this time, the antibacterial substance (B-1) was added so that the mass ratio of (meth)acrylate polymer (A-1) to the total mass of antibacterial substance (B-1) was 17.4% by mass. A 50 mm × 50 mm × 0.3 mm polycarbonate sheet was immersed in the obtained surface treatment agent for 5 seconds, then the sheet was removed and dried at 60°C for 24 hours to prepare a pre-aging sample. Furthermore, the sample was aged in physiological saline at 37°C for 7 days to prepare a post-aging sample. The results of examining the antibacterial activity against Pseudomonas aeruginosa before and after aging are summarized in Table 2.
[0091] (Example 2) A surface treatment agent was prepared by dissolving (meth)acrylate polymer (A-2) in ethanol to a solid content concentration of 3 wt%, then adding the silver-based glass antibacterial agent "Ion Pure (manufactured by Ishizuka Glass Co., Ltd.)" as the antibacterial substance (B-2), and stirring with an ultrasonic device for 5 minutes. The antibacterial substance (B-2) was added so that its mass ratio to the total mass of (meth)acrylate polymer (A-2) and antibacterial substance (B-2) was 0.8% by mass. A 50 mm × 50 mm × 0.3 mm polycarbonate sheet was immersed in the obtained surface treatment agent for 5 seconds, then the sheet was removed and dried at 60°C for 24 hours to prepare a pre-aging sample. Furthermore, the sample was aged in physiological saline at 37°C for 7 days to prepare a post-aging sample. The results of examining the antibacterial activity against Pseudomonas aeruginosa before and after aging are summarized in Table 2.
[0092] (Example 3) A surface treatment agent was prepared by dissolving (meth)acrylate polymer (A-3) in ethanol to a solid content concentration of 3 wt%, then adding the zinc oxide-based antibacterial agent "SEABIO Z-24 (manufactured by New Lime Co., Ltd.)" as the antibacterial substance (B-3), and stirring with an ultrasonic device for 5 minutes. The antibacterial substance (B-3) was added so that its mass ratio to the total mass of (meth)acrylate polymer (A-3) and antibacterial substance (B-3) was 3.4% by mass. A 50 mm × 50 mm × 0.3 mm polycarbonate sheet was immersed in the obtained surface treatment agent for 5 seconds, then the sheet was removed and dried at 60°C for 24 hours to prepare a pre-aging sample. Furthermore, the sample was aged in physiological saline at 37°C for 7 days to prepare a post-aging sample. The results of examining the antibacterial activity against Pseudomonas aeruginosa before and after aging are summarized in Table 2.
[0093] (Example 4) A surface treatment agent was prepared by dissolving (meth)acrylate polymer (A-4) in ethanol to a solid content concentration of 3 wt%, then adding the organic antibacterial agent "chlorhexazine" as the antibacterial substance (B-4), and stirring with an ultrasonic device for 5 minutes. The antibacterial substance (B-4) was added in such a mass ratio of 5.0% by mass to the total mass of (meth)acrylate polymer (A-4) and antibacterial substance (B-4). A 50 mm × 50 mm × 0.3 mm polycarbonate sheet was immersed in the obtained surface treatment agent for 5 seconds, then the sheet was removed and dried at 60°C for 24 hours to prepare a pre-aging sample. Further aging was performed in physiological saline at 37°C for 7 days to prepare a post-aging sample. The results of examining the antibacterial activity against Pseudomonas aeruginosa before and after aging are summarized in Table 2.
[0094] (Example 5) A surface treatment agent was prepared by dissolving (meth)acrylate polymer (A-1) in ethanol to a solid content concentration of 3 wt%, then adding the silver-based zeolite antibacterial agent "Zeomic Type A (manufactured by Sinanen Zeomic Co., Ltd.)" as the antibacterial substance (B-5), and stirring with an ultrasonic device for 5 minutes. The antibacterial substance (B-5) was added in such a mass ratio of 4.2% by mass to the total mass of (meth)acrylate polymer (A-1) and antibacterial substance (B-5). A 50 mm × 50 mm × 0.3 mm polycarbonate sheet was immersed in the obtained surface treatment agent for 5 seconds, then the sheet was removed and dried at 60°C for 24 hours to prepare a pre-aging sample. Furthermore, the sample was aged in physiological saline at 37°C for 7 days to prepare a post-aging sample. The results of examining the antibacterial activity against Pseudomonas aeruginosa before and after aging are summarized in Table 2.
[0095] (Example 6) A surface treatment agent was prepared by dissolving (meth)acrylate polymer (A-2) in ethanol to a solid content concentration of 3 wt%, then adding the silver-based phosphate antibacterial agent "Silver Ace B300K (manufactured by Taihei Chemical Industry Co., Ltd.)" as the antibacterial substance (B-6), and stirring with an ultrasonic device for 5 minutes. The antibacterial substance (B-6) was added so that its mass ratio to the total mass of (meth)acrylate polymer (A-2) and antibacterial substance (B-6) was 13.2% by mass. A 50 mm × 50 mm × 0.3 mm polycarbonate sheet was immersed in the obtained surface treatment agent for 5 seconds, then the sheet was removed and dried at 60°C for 24 hours to prepare a pre-aging sample. Furthermore, the sample was aged in physiological saline at 37°C for 7 days to prepare a post-aging sample. The results of examining the antibacterial activity against Staphylococcus aureus before and after aging are summarized in Table 2.
[0096] (Example 7) A surface treatment agent was prepared by dissolving (meth)acrylate polymer (A-4) in ethanol to a solid content concentration of 3 wt%, then adding zinc oxide-based antimicrobial agent "ABZ-10-KS (manufactured by Sakai Chemical Co., Ltd.)" as the antimicrobial substance (B-7), and stirring with an ultrasonic device for 5 minutes. The antimicrobial substance (B-7) was added so that its mass ratio to the total mass of (meth)acrylate polymer (A-4) and antimicrobial substance (B-7) was 1.3% by mass. A 50 mm × 50 mm × 0.3 mm polycarbonate sheet was immersed in the obtained surface treatment agent for 5 seconds, then the sheet was removed and dried at 60°C for 24 hours to prepare a pre-aging sample. Furthermore, the sample was aged in physiological saline at 37°C for 7 days to prepare a post-aging sample. The results of the investigation of antimicrobial activity against E. coli before and after aging are summarized in Table 2.
[0097] (Comparative Example 1) A surface treatment agent was prepared by dissolving (meth)acrylate polymer (A-1) in ethanol to a solid content concentration of 3 wt%, then adding the silver nanoparticle antibacterial agent "NanoPure (manufactured by Nippon Ion Co., Ltd.)" as the antibacterial substance (B-8), and stirring with an ultrasonic device for 5 minutes. The antibacterial substance (B-8) was added so that its mass ratio to the total mass of (meth)acrylate polymer (A-1) and antibacterial substance (B-8) was 0.3% by mass. A 50 mm × 50 mm × 0.3 mm polycarbonate sheet was immersed in the obtained surface treatment agent for 5 seconds, then the sheet was removed and dried at 60°C for 24 hours to prepare a pre-aging sample. Furthermore, the sample was aged in physiological saline at 37°C for 7 days to prepare a post-aging sample. The results of examining the antibacterial activity against Pseudomonas aeruginosa before and after aging are summarized in Table 2.
[0098] (Comparative Example 2) A surface treatment agent was prepared by dissolving (meth)acrylate polymer (A-2) in ethanol to a solid content concentration of 3 wt%, then adding the silver complex antimicrobial agent "AG Alpha CF-01 (manufactured by MGC Woodchem Co., Ltd.)" as the antimicrobial substance (B-9), and stirring with an ultrasonic device for 5 minutes. The antimicrobial substance (B-9) was added so that its mass ratio to the total mass of (meth)acrylate polymer (A-2) and antimicrobial substance (B-9) was 2.6% by mass. A 50 mm × 50 mm × 0.3 mm polycarbonate sheet was immersed in the obtained surface treatment agent for 5 seconds, then the sheet was removed and dried at 60°C for 24 hours to prepare a pre-aging sample. Furthermore, the sample was aged in physiological saline at 37°C for 7 days to prepare a post-aging sample. The results of examining the antimicrobial activity against Pseudomonas aeruginosa before and after aging are summarized in Table 2.
[0099] (Comparative Example 3) A surface treatment agent was prepared by dissolving (meth)acrylate polymer (A-5) in ethanol to a solid content concentration of 3 wt%, then adding the antibacterial substance (B-2), a silver-based glass antibacterial agent "Ion Pure (manufactured by Ishizuka Glass Co., Ltd.)," and stirring with an ultrasonic device for 5 minutes. The antibacterial substance (B-2) was added in such a mass ratio of 0.8 mass% to the total mass of (meth)acrylate polymer (A-5) and antibacterial substance (B-2). A 50 mm × 50 mm × 0.3 mm polycarbonate sheet was immersed in the obtained surface treatment agent for 5 seconds, then the sheet was removed and dried at 60°C for 24 hours to prepare a pre-aging sample. Furthermore, the sample was aged in physiological saline at 37°C for 7 days to prepare a post-aging sample. The results of examining the antibacterial activity against Pseudomonas aeruginosa before and after aging are summarized in Table 2.
[0100] (Comparative Example 4) A surface treatment agent was prepared by dissolving (meth)acrylate polymer (A-6) in ethanol to a solid content concentration of 3 wt%, then adding the zinc oxide-based antimicrobial agent "SEABIO Z-24 (manufactured by New Lime Co., Ltd.)" as the antimicrobial substance (B-3), and stirring with an ultrasonic device for 5 minutes. The antimicrobial substance (B-3) was added so that its mass ratio to the total mass of (meth)acrylate polymer (A-6) and antimicrobial substance (B-3) was 3.4% by mass. A 50 mm × 50 mm × 0.3 mm polycarbonate sheet was immersed in the obtained surface treatment agent for 5 seconds, then the sheet was removed and dried at 60°C for 24 hours to prepare a pre-aging sample. Furthermore, the sample was aged in physiological saline at 37°C for 7 days to prepare a post-aging sample. The results of examining the antimicrobial activity against E. coli before and after aging are summarized in Table 2.
[0101] Table 1 summarizes the composition and properties of the polymers produced in the manufacturing examples.
[0102] [Table 1]
[0103] The results of the blood compatibility and antibacterial activity evaluations in the examples and comparative examples are summarized in Table 2.
[0104] [Table 2]
[0105] Examples 1-7 showed favorable results in blood compatibility tests, with low platelet adhesion counts on the sample surface. Furthermore, complement activity inhibitory effects were observed in complement titer evaluation. Antimicrobial activity was observed before and after aging in antimicrobial activity tests, and the appearance after coating was also good before and after aging in the appearance test. Therefore, it is believed that medical devices coated with the antithrombotic antimicrobial composition of the present invention will maintain long-term antimicrobial properties and exhibit minimal discoloration over time.
[0106] On the other hand, Comparative Examples 1 and 2 showed poor appearance after coating and aging. Furthermore, Comparative Examples 3 and 4 showed poor results in the blood compatibility test, with numerous platelets adhering to the sample surface in a pile-up fashion.
Claims
1. (Meth)acrylate copolymer (A) comprising alkyl (meth)acrylate units represented by the following general formula 1 and / or silicone (meth)acrylate units represented by the following general formula 2, and methoxypolyethylene glycol (meth)acrylate units represented by the following general formula 3. and, An antithrombotic antibacterial composition comprising at least one antibacterial substance (B) selected from the group consisting of silver-based inorganic antibacterial agents, zinc oxide-based antibacterial agents, and organic antibacterial agents. 【Chemistry 1】 (In the formula, R1 represents an alkyl group having 2 to 30 carbon atoms or an aralkyl group having 7 to 30 carbon atoms, and R2 represents a hydrogen atom or a methyl group.) 【Chemistry 2】 (In the formula, R3 is a hydrogen atom or a methyl group, R4 is an alkylene group having 1 to 6 carbon atoms, R5 is an alkyl group having 1 to 6 carbon atoms, and n is in the range of 1 to 1,000.) 【Transformation 3】 (In the formula, R6 represents a hydrogen atom or a methyl group, and m represents a range of 2 to 1,000.)
2. The antithrombotic antibacterial composition according to claim 1, wherein the antibacterial substance (B) is at least one antibacterial substance selected from silver-based glass antibacterial agents, silver-based zeolite antibacterial agents, and silver-based phosphate antibacterial agents.
3. The antithrombotic antibacterial composition according to claim 1, wherein the silver-based inorganic antibacterial agent is an inorganic compound supported with silver and / or silver ions.
4. The antithrombotic antibacterial composition according to claim 1, characterized in that the (meth)acrylate copolymer (A) contains alkyl (meth)acrylate units represented by general formula 1 and / or silicone (meth)acrylate units represented by general formula 2 and methoxypolyethylene glycol (meth)acrylate units represented by general formula 3 in a molar ratio of (formula 1 + formula 2) / formula 3 = 30 to 90 / 10 to 70.
5. The antithrombotic antibacterial composition according to claim 1, wherein the (meth)acrylate copolymer (A) is soluble in any of the alcohols having 1 to 6 carbon atoms.
6. The antithrombotic antibacterial composition according to claim 1, wherein the glass transition temperature of the (meth)acrylate copolymer (A) is -100 to 20°C.
7. The antithrombotic antibacterial composition according to claim 1, wherein the number average molecular weight of the (meth)acrylate copolymer (A) is 2,000 to 200,000.
8. The antithrombotic antibacterial composition according to claim 1, characterized in that the antibacterial substance (B) is contained in an amount of 0.1% to 50.0% by mass relative to the antithrombotic antibacterial composition.
9. The antithrombotic antibacterial composition according to claim 1, characterized in that the antibacterial activity value evaluated based on JIS Z 2801 is 1.3 or higher.
10. A coating agent containing the antithrombotic antibacterial composition according to any one of claims 1 to 9.
11. A medical device characterized in that at least a portion of the blood-contacting portion is coated with the antithrombotic antibacterial composition described in any one of claims 1 to 9.
Citation Information
Patent Citations
Senzainoyusosochi
JP1976014660A
Catheter having infection resistance
JP1998211272A
Production of polymer containing hydrophobic group and phosphorylcholine group
JP1999035605A
Surface protective agent
JP1999287802A
Antibacterial catheter
JP2005334216A